Healthcare, Insurance, and You The Savvy Consumers Guide - Zamosky, Lisa. (Apress : Imprint: Apress, 2013)
Healthcare is changing and you need to know howand what to do about it. Getting good medical care shouldnt be so confusingor so costly.Healthcare, Insurance, and Yousimplifies the many confusing details about our healthcare system so you can make informed decisions. Result? Better health at lower cost. With the advent of healthcare reform, things are changingespecially when it comes to insurance.Most people will now have to buy insurance. Do you know where to get a policy or what to look for in one? Did you know more people will now qualify for free or subsidized healthcare? Even if you get insurance through work, you'll face new choices that you'd better understand to maintain your peace of mind. As this book shows, the failure to understand how insurance and the healthcare system work can have a major impact on your physical and financial health. Healthcare, Insurance, and Youis aneasy-to-use guide that explains the main challenges you face when trying to get excellent healthcare: choosing the best insurance policy for your situation, finding the right doctor or hospital, buying prescription drugs the least expensive way, picking out the right Medicare plan, or fighting for your rights when dealing with insurers or medical providers. Healthcare, Insurance, and You includes tips, resources, and strategies for navigating the healthcare system and avoiding common mistakes so you can get the best healthcare for you, your family, or your organization without breaking the bank.This book shows you: How to choose a health plan that best meets your medical and financial needs, including new options under the Affordable Care Act Ways to cut through red tape andfight billing errors and claim denials Whatbusinesses need to know about offeringor not offeringinsurance to employees How to plan ahead for a disability or for end-of-life care Healthcare costs rank high on the list of money concerns Americans have. And when it comes to getting great healthcare for you and your family and avoidingcrippling medical bills, knowledge is power. Healthcare, Insurance, and You is a practical guide that explains the complicated healthcare system in plain languageand puts the power of good health back in your hands.